Interactive solat learning for children using metaphor technique / Kartini Mohd Zukri - Mohd Zukri, Kartini (2010)
Despite human computer interaction have many techniques, only a few focus developing on the metaphor technique for children courseware learning and most the children perceptions of the interface are not considerate from the developer that gives the children difficulties to use software. This project is intent to developed interactive prayer learning for children using metaphor technique that to give better understanding and familiar to children when using the courseware. The objective of studying this is to observe the suitable metaphor for children from books, video learning, article, journal and website that related with the children learning. The observation was analyze according three types of icons were used regarding the text-image, button and navigation. By using metaphor technique it will increase the familiarity with the interface, motivates the user to explore, maintain consistency in interface and help novices to quickly learn how to use this interactive prayer learning.